Endometrial microbiota alteration in female patients with endometrial polyps based on 16S rRNA gene sequencing analysis - Zhao, Yu; Liao, Yun; Xu, Gufeng; Wang, Yue (Frontiers in Cellular and Infection Microbiology, 2024)
The potential role of the endometrial microbiome in the pathogenesis of endometrial polyps (EPs) warrants further investigation, given the current landscape of limited and inconclusive research findings. We aimed to explore the microecological characteristics of the uterine cavity in patients with EPs and investigate the potential of endometrial microbiota species as novel biomarkers for identifying EPs. Methods: Endometrial samples were collected from 225 patients who underwent hysteroscopies, of whom 167 had EPs, whereas 58 had non-endometrial hyperproliferative endometrium status. The endometrial microbiota was assessed using 16S rRNA gene sequencing. We characterized the endometrial microbiome and identified microbial biomarkers for predicting EPs. Results: The endometrial microbial diversity and composition were significantly different between the EP and control groups. Functional analyses of the endometrial microbiota demonstrated significant alterations in pathways involved in sphingolipid metabolism, steroid hormone biosynthesis, and apoptosis between the two groups. Moreover, a classification model based on endometrial microbial ASV-based biomarkers along with the presence of abnormal uterine bleeding symptoms achieved powerful classification potential in identifying EPs in both the discovery and validation cohorts. Conclusion: Our study indicates a potential association between altered endometrial microbiomes and EPs. Endometrial microbiota-based biomarkers may prove valuable for the diagnosis of EPs.